FAKTOR PENYEBAB PERILAKU MEROKOK DI SMK AKBAR KOTA PEKANBARU - Rosmeri Br Bukit (Ensiklopedia of Journal, 2019)
Smoking is one behavior that is very detrimental to health. Smoking can cause various diseases such as high blood pressure and heart problems caused by the effects of chemicals contained in cigarettes such as nicotine and tar. Based on data from The Tobacco Atlas in 2015 that Indonesia is the country with the highest smoking rates in the world. The purpose of this study was to determine the relationship between the factors causing the behavior of smoking students at the Akbar Vocational School in the City of Pekanbaru. This research is quantitative descriptive which aims to explain the causes of smoking students behavior in the Akbar Vocational High School in Pekanbaru in 2019. The samples in this study were 38 respondents using Simple Random Sampling with the chi-square test. The results of this study showed 17 people (44.7%) smoking students and 21 people (55.3%). Variables related to smoking behavior are knowledge, attitudes and actions. Based on the results of the study it can be concluded that there is a relationship between knowledge, attitudes and actions towards smoking behavior that can be influenced by the surrounding environment so that respondents try to smoke.